DEVELOPING REFLECTIVE WEBBED THEMATIC LEARNING DOCUMENTS TO FOSTER CRITICAL THINKING SKILL (Universitas Ivet, 2015)
The questioner that was given for 20 science teachers of SMP shows that only 20% teacher reflects their lesson plan before applicated to the next class. This fact indicates that the teacherâ€™s reflection awarness is low. The other problem founded in former research is 70% teacher feels hard to carry meaningful learning.The aims of this study is for developing the reflective webbed-thematic learning documents to learn the relationship between photosynthesis and global warming that is valid and reliable to be applicate on SMP GradeÂ VIII. This learning documents can helps the teacher to do reflection and foster the critical thinking skill. This study is Research and Development which consist of four steps (Define, Design, Develop, and Dessiminate) that is modificated. On the develop stage the learning documents are reflected three times to produce the final product. The implementation of learning document could develop the critical thinking skill. The second meeting gave the best score for critical thinking skill. The open-ended question developed can motivates the students to express their prediction and argument. The implementation learning documents which mainly focuse on reflection has sucessfully improve the quality of teaching and learning process. It caused by the teachers were already knew the weakness and the correct it.Â Keywords: Critical thinking skill, webbed thematic learning, reflective lerrning, photosynthesis, global warming